PENYULUHAN UPAYA PENCEGAHAN PENYALAHGUNAAN NARKOBA TERHADAP REMAJA PUTRA DI KELURAHAN SIMATORKIS SISOMA ANGKOLA BARAT - Ritonga, Nefonavratilova (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
Drug abuse among adolescents is very concerning, especially among school age. Based on research results in 2020, it showed that 3.21% of students had used drugs or the equivalent of 2,297,492 students had abused drugs. Curiosity and trial and error occupy the top position by 64% as reason students take drugs. The rest were due to having fun (16.8%), being persuaded by friends (6.6%), being framed (2.3%), and personal stress factors (5.6%). It is not easy to unravel the problem of drug abuse among adolescents. One of efforts to reduce level of drug abuse among students is by providing information about dangers of drugs through outreach to schools. So that students become more alert and able to bridge themselves from snares of drugs. This activity is carried out with counseling, guidance and outreach about dangers of drugs and efforts to prevent drugs from entering Young Men of Simatorkis Sisoma Village so that all elements in the Simatorkis District can be aware of spread of drugs. The counseling media used is in form of Power Point which is easy for teenagers to see together and provides an understanding of the dangers of drugs both in the short and long term. The output of this programwas expected to be able to have an impact on the realization of schools that are free from drug trafficking and students who are clean from drug abuse.